The Effectiveness of E-Procurement in Implementing the Procurement of Goods and Services in the Surabaya City Government - Dharmawan, Widya; Widiyarta, Agus (Universitas Muhammadiyah Ponorogo, 2025)
The Surabaya City Government's form of e-government is by implementing e-procurement in the procurement of goods and services (auction). E-procurement is an innovation from conventional procurement to electronic-based procurement of goods and services. technology will be very important in public services in the future by The Surabaya government understands that the role of digital Encouraging service acceleration and reducing budgets with information technology. The purpose of this study is to determine whether e-procurement has been effective in its application in the Surabaya city government. The research method used is descriptive qualitative research with reference to various references. The focus of the research uses Richard M. Steers' theory of effectiveness which measures effectiveness using indicators of goal achievement, integration and adaptation. Data collection techniques are interviews, observation and documentation. The technique of determining informants is purposive sampling technique and snowball sampling which is expected to be a source of information for researchers. The data analysis technique uses interactive data developed by Miles Hubberman, namely Data Collecting, Data Condensation, Data Display, Conclutions and Verifying. Data validity uses credibility tests, namely extension of observation, data triangulation and using reference materials which in this credibility test are expected to be able to provide accurate and valid data.